Pharmacophore-Based Virtual Screening from Indonesian Herbal Database to Find Putative Selective Estrogen Receptor Degraders - Prawiningrum, Aisyah F; Paramita, Rafika Indah; Erlina, Linda (Indonesian Journal of Medical Chemistry and Bioinformatics, 2022)
Most breast cancer cases are luminal subtypes which are estrogen receptor-sensitive or progesterone receptor-sensitive. Common treatments include surgery and adjuvant endocrine therapy by prescribing selective estrogen receptor degraders (SERD). SERD is a type of medication that inhibits estrogen receptor (ER) activity by degrading it, and as a result, downregulating it. The current FDA-approved SERD can only be administered through intramuscular injection. The aim of this study is to find orally non-toxic and bioavailable herbal alternatives of SERDs in Indonesian Herbal Database by doing virtual screening using LigandScout. The hit compounds were further analyzed using a molecular docking tool, AutoDock. Three compounds that gave the best results in molecular docking, namely kuwanon T, mulberrin, and curcumin, were analyzed in terms of their toxicity and drug-likeness. Based on toxicity and drug-likeness study, curcumin is considered to be the best candidates for SERD alternatives. This result is further supported by molecular dynamic simulation outcome in which curcumin is the most stable while binding with estrogen receptors.